2019
DOI: 10.1097/inf.0000000000002387
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation of Influenza in Children 6 to 35 Months of Age

Abstract: Background: In an exploratory analysis of an inactivated quadrivalent influenza vaccine (IIV4) trial in children 6–35 months without risk factors for influenza, we evaluated clinical presentation of influenza illness and vaccine impact on health outcomes. Methods: This phase III trial was conducted in 13 geographically diverse countries across 5 influenza seasons (2011–2014). Children were randomized 1:1 to IIV4 or control. Active surveillance was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 41 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Namely, most vaccine efficacy studies have focused on outcomes of any symptomatic influenza and not disease attenuation in vaccinated versus unvaccinated groups. A few clinical trials of inactivated and live-attenuated influenza vaccines in children have demonstrated higher efficacy against laboratory-confirmed influenza with severe endpoints (defined mostly by fever) compared with influenza of any severity [ 9 , 82 , 83 ]. Findings from observational studies in general have been inconsistent possibly due to differences in outcomes, sample size, age differences, and influenza season.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, most vaccine efficacy studies have focused on outcomes of any symptomatic influenza and not disease attenuation in vaccinated versus unvaccinated groups. A few clinical trials of inactivated and live-attenuated influenza vaccines in children have demonstrated higher efficacy against laboratory-confirmed influenza with severe endpoints (defined mostly by fever) compared with influenza of any severity [ 9 , 82 , 83 ]. Findings from observational studies in general have been inconsistent possibly due to differences in outcomes, sample size, age differences, and influenza season.…”
Section: Discussionmentioning
confidence: 99%
“…According to a clinical trial carried out in 2018 on 6–35 months old children, individuals receiving quadrivalent Influenza vaccines showed a 47% lower incidence of influenza compared to the placebo group ( Table 1 ). This outcome was accompanied by a 50% reduced antibiotic prescription [ 32 ].…”
Section: Effect Of Vaccines On Amrmentioning
confidence: 99%